Realisme magis dalam Roman Steinernes Fleisch karya Cornelia Funke menurut perspektif Wendy B. Faris - Jannah, Anna Nurbayti; Setiawan, Akbar Kuntardi (Journal of Culture, Literature and Foreign Language Teaching, 2024)
Penelitian ini bertujuan untuk mendeskripsikan karakteristik elemen, gradasi tiap elemen, relasi antar elemen, dan kadar realisme magis roman Steinernes Fleisch karya Cornelia Funke. Penelitian ini menggunakan metode kualitatif dengan pendekatan realisme magis. Sumber data berasal dari roman Steinernes Fleisch karya Cornelia Funke. Data diperoleh dengan teknik baca dan catat. Data dianalisis dengan teknik deskriptif kualitatif. Keabsahan data diperoleh melalui validitas semantik. Penelitian ini menggunakan reliabilitas interrater dan intrarater. Hasil penelitian pada roman ini menunjukkan bahwa (1) roman ini memiliki lima karakteristik realisme magis dalam perspektif Wendy B. Faris, yaitu (a) the irreducible element (b) the phenomenal world, (c) unsettling doubts, (d) merging realms dan (e) distruption of identity. (2) Gradasi tiap elemen: terdapat perbedaan yang jelas di antara kelima elemen realisme magis. (3) Relasi antar elemen realisme magis: terdapat sebuah struktur yang saling terhubung dan mempengaruhi sebagai sebuah unsur pembangun cerita. (4) Dilihat dari kemunculan seluruh tokoh, objek, dan peristiwa dalam Roman Steinernes Fleisch, menunjukkan isi realisme magis dengan kadar yang kuat.   Magical realism in Cornelia Funke’s novel Steinernes Fleisch, according to Wendy B. Faris’s perspective   Abstract: This research aims to describe the characteristics of the elements, the gradation of each element, the relationship between elements, and the level of magical realism and the level of magical realism in Cornelia Funke’s Novel entitled Steinernes Fleisch. This research is qualitative research that produces descriptive data using the magical realism approach. The data were obtained using reading and note-taking techniques. The data were analyzed using qualitative descriptive techniques. Data validity was obtained through semantic validity. This research uses interrater and interrater reliability. The result of this study on romance suggests that (1) this romance has five characteristics of magical realism, according to Wendy F. Faris: (a) the irreducible element, (b) the phenomenal world, (c) unsettling doubts, (d) merging realms and (e) disruption of identity. (2) Element’s graduation: there is a clear distinction between the slings of the magical realism element. (3) The connections between magical realism elements: there is a structure that is connected and affected as a story builder. (4) The appearances of all these characters, objects, and events in the romance Steinernes Fleisch indicate a strong level of magical realism.